4-Methoxycinnamyl p-Coumarate Mediates Anti-Atherosclerotic Effects by Suppressing NF-ĸB Signaling Pathway and Foam Cell Formation - Poonasri, Mayuree; Sawai, Petcharat; Srisook, Klaokwan (Trends in Sciences, 2025)
Vascular inflammation plays a crucial role in atherosclerosis initiation and progression. 4-methoxycinnamyl p-coumarate (MCC), a major bioactive phenylpropanoid found in Etlingera pavieana rhizomes, has demonstrated anti-inflammatory activity in lipopolysaccharide-induced macrophages and microglial cells. Therefore, we hypothesized that MCC may also exert anti-inflammatory effects on human vascular endothelial cells, which are key players in the early stages of atherosclerotic plaque formation. To test this hypothesis, we investigated the mechanisms underlying MCC-mediated anti-atherosclerotic effects in tumor necrosis factor-alpha (TNF-α)-treated vascular endothelial cells. An MTT assay was performed to assess the cytotoxicity of MCC on human vascular endothelial EA.hy926 cells. The mRNA expression levels of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) were analyzed using real-time reverse transcription polymerase chain reaction. Foam cell formation induced by oxidized low-density lipoprotein (ox-LDL) in RAW264.7 macrophages was evaluated by Oil Red O staining. Our findings revealed that non-toxic concentrations of MCC (6.25 - 25 µM) significantly downregulated ICAM-1 and VCAM-1 mRNA expression in a concentration-dependent manner. In addition, MCC inhibited the nuclear translocation of the nuclear factor-κB (NF-κB) p65 subunit, as demonstrated by western blot analysis. Moreover, MCC reduced ox-LDL-induced foam cell formation in RAW264.7 macrophages. Collectively, these results suggest that MCC exerts its anti-atherosclerotic effects by downregulating ICAM-1 and VCAM-1 expression via inhibition of the NF-κB signaling pathway in endothelial cells and by suppressing formation of ox-LDL-induced foam cells. These findings highlight the potential of MCC as a promising therapeutic agent for the treatment of vascular inflammatory disorders. HIGHLIGHTS 4-methoxycinnamyl p-coumarate (MCC) reduces ICAM-1 and VCAM-1 expression in TNF-α-stimulated endothelial cells. MCC inhibits NF-κB p65 nuclear translocation, blocking inflammatory signaling. MCC suppresses ox-LDL-induced foam cell formation in macrophages. GRAPHICAL ABSTRACT